AN ERROR ANALYSIS IN WRITING RECOUNT TEXT AT SMPN 02 SEPAUK - Tuti Tuti; Ilinawati Ilinawati; Edi Saputra (INOVISH JOURNAL, 2022)
The main problem of this research is the researcher wants to analyze the students' errors in writing recount text. This research aims to find out the error made by students in writing recount text. The subject of this research is 22 students writing products in writing recount text. The method used in this research is a qualitative research approach, the technique of data collection only using documentation, the document is the student's test results in writing recount text. The qualitative data were analyzed through assembling the data, coding the data, comparing the data, building interpretations, and reporting the outcomes. Based on the research finding, the researcher found three types of errors made by students in writing recount text: error of omissionÂ  54,9%, error of misinformationÂ  19,6%, error of misordering 25,5%. Based on the finding, the researcher found omission error was a dominant error made by eight grade students of SMP Negeri 02 Sepauk.